Digital Transformation and Destination Branding as Drivers of Destination Brand Experience: Evidence from Medan City, Indonesia - Maulidina Maulidina; Onan Marakali Siregar; Sri Eka Wulandari; Hidayah Yoanna Putri (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
The rapid advancement of digital technologies has transformed the tourism industry, requiring tourism destinations to strengthen their digital capabilities and branding strategies to create memorable visitor experiences. Despite the growing attention given to Digital Transformation and Destination Branding, empirical evidence examining their combined effects on Destination Brand Experience remains limited, particularly within the context of urban tourism destinations in Indonesia. Therefore, this study aims to examine the effects of Digital Transformation and Destination Branding on Destination Brand Experience among tourists visiting tourism destinations in Medan City, Indonesia. A quantitative explanatory research design was employed using a cross-sectional survey. Data were collected from 150 tourists through purposive sampling using a structured questionnaire. The data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis with IBM SPSS Statistics. The findings indicate that both Digital Transformation and Destination Branding have positive and significant effects on Destination Brand Experience. Digital Transformation positively influences tourists' experiences by enhancing digital communication, service accessibility, tourist interaction, and personalized tourism services. Likewise, Destination Branding strengthens destination identity, emotional attachment, perceived uniqueness, and effective communication, thereby improving tourists' overall destination experiences. The regression model demonstrates satisfactory explanatory power, indicating that both independent variables jointly contribute to explaining Destination Brand Experience. This study contributes to tourism marketing literature by integrating Digital Transformation and Destination Branding within a unified conceptual framework and provides practical implications for tourism destination managers and policymakers in developing digitally integrated and experience-oriented urban tourism destinations.